Validity and reliability of the social entrepreneurial personality - Radin A Rahman, Radin Siti Aishah; Lope Pihie, Zaidatol Akmaliah (2014)
Apart from business entrepreneurs, social entrepreneurs have the ability to significantly mobilise economic development mechanism in many third world countries and sustain the living of those who are marginalized. Most researchers discovered mutual traits between both business entrepreneurs and social entrepreneurs (Martin & Osberg, 2007: 37; Ernst, 2012: 60). The gap between the fixed goals from solely reaping maximum profit to being socially oriented has become the measuring tool in research dynamic traits possessed by these social entrepreneurs. Hence, this research seeks to determine the validity and reliability of social entrepreneurial personality among 784 Enactus students in 31 public and private institutions of higher learning in Malaysia. Enactus conducts social entrepreneurial activities through community development projects in each of Malaysia’s higher institution of education. Hence, the combination between entrepreneurial orientation and prosocial results in social entrepreneurial personality (Ernst, 2012: 56) that is predominantly based on the theory of planned behaviour (Ajzen, 1991: 182). Prosocial oriented personality is understood as being conscientious and benefitting others. It encompasses the elements of empathy and social responsibility. Instead, personality that is based on entrepreneurship combines the stable entrepreneurial traits including pro-activeness, risk-taking propensity, and innovativeness. Confirmatory factor analysis (CFA) was used to assess unidimensionality, validity, reliability and fitness of social entrepreneurial model. The personality item reached the Cronbach’s alpha value greater than 0.70 for the reliability of two sub-constructs. This item also obtained a consistent and good internal validity, which was convergent and discriminant validity. The goodness-of-fit was achieved with high construct validity. The findings have important implications for the new development of social entrepreneurial personality instrument.